Homecare: a strategy to ease the burden of Family Care Givers of clients with mental disorders: an overview - Mathew, Suja Chungathil; Mathias, Thereza (International Journal Of Community Medicine And Public Health, 2021)
Mental disorders are the second leading cause of disease burden in terms of Years Lived with Disability (YLDs) and the sixth leading cause of Disability-Adjusted Life-Years (DALYs) in the world in 2017. Mental disorders can lead to extreme physical, psychological, social and financial burden among the caregivers. Family is a basic unit of caring for the mentally ill. Empowering the family caregivers on caring their mentally ill client at home is an effective strategy in rehabilitation as the mental health facilities are limited in India. Home based care is known to reduce burden among the caregivers. Homecare includes various components that help in caring and managing clients with Activities of Daily Living (ADL), supervision and administration of medication, recreation and leisure activity, stress management, regular follow up with mental health professional, social skill training, management of psychiatric emergencies, management of potentially harmful behaviours such as suicide and anger management. The outcome of the home care of mentally ill depends on the willingness and cooperation of the family and continuous support and monitoring by the mental health team. It is cost-effective and implies the shift of responsibility not only on the hospital but on the family caregivers and the health professionals in the community.